Students' Perceptions and Attitudes Toward the Use of Communicative Language Teaching (CLT) in Improving English Speaking Skill - Latif, Saiful; Dahlan, Suratman (STAIN Majene, 2024)
Communicative Language Teaching (CLT) is an instructional approach that prioritizes the development of communication skills, utilizing language in contexts relevant to daily activities. However, its application, particularly in English speaking lessons, presents various challenges and difficulties for students. The primary objective of this study was to explore students' perceptions and attitudes toward the use of CLT in improving English speaking skill. This research adopted a descriptive quantitative design, with participants consisted of 55 third-semester students from the English Education Study Program at Universitas Khairun. Data were gathered through a Google Form survey containing a Likert scale-based questionnaire with 20 items. The data were subsequently analyzed by using mean scores and percentage distributions. The findings revealed that students generally held a positive view of CLT in English speaking instruction, as evidenced by an overall mean score of 3.79, corresponding to a